2017
DOI: 10.1111/cup.12994
|View full text |Cite
|
Sign up to set email alerts
|

Miniaturization of sebaceous glands: A novel histopathological finding in pemphigus vulgaris and pemphigus foliaceus of the scalp

Abstract: Follicular acantholysis is a common histopathological feature of pemphigus. It may serve as a clue to the diagnosis of pemphigus subtypes, as PV and PF differ in the depth of follicular acantholysis. The miniaturization of sebaceous glands is a common histopathological feature observed in scalp specimens of patients with pemphigus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 26 publications
1
14
0
Order By: Relevance
“…reported acantholysis extending from the infundibulum to the suprabulbar region in anagen hair follicles in patients with PV and progressive hair loss . Our recent findings confirm that acantholysis is located along the outer root sheath of the hair follicle in patients with PV …”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…reported acantholysis extending from the infundibulum to the suprabulbar region in anagen hair follicles in patients with PV and progressive hair loss . Our recent findings confirm that acantholysis is located along the outer root sheath of the hair follicle in patients with PV …”
Section: Discussionsupporting
confidence: 86%
“…4 Our recent findings confirm that acantholysis is located along the outer root sheath of the hair follicle in patients with PV. 14 Follicular acantholysis may be explained by the distribution of desmogleins in the structure of the hair follicle. 1 Dsg1 is expressed in the inner root sheath, in the innermost layers of the outer root sheath, and in epidermal suprabasal cells, 1 whereas expression of Dsg3 in the hair follicle depends on keratinization type.…”
Section: Discussionmentioning
confidence: 99%
“…A case report of pemphigus foliaceus by Mlynek et al described acantholysis which was observed in the infundibular outer root sheath, sparing its infrainfundibular part [ 25 ]. In our recent study performed on 32 patients with pemphigus, we observed that follicular acantholysis is a common feature of both types of pemphigus occurring in 12/17 (70.6%) patients with pemphigus vulgaris and 12/15 (80.0%) patients with pemphigus foliaceus [ 42 ]. We also confirmed that pemphigus vulgaris and pemphigus foliaceus differ as regards the depth of acantholysis.…”
Section: Resultsmentioning
confidence: 99%
“…We also confirmed that pemphigus vulgaris and pemphigus foliaceus differ as regards the depth of acantholysis. Acantholysis extended down the entire length of the outer root sheath of the hair follicle in pemphigus vulgaris, whereas in pemphigus foliaceus acantholysis was restricted to the infundibulum [ 42 ]. Acantholysis was also observed in vellus hair follicles in 12/17 (70.6%) patients with pemphigus vulgaris and 9/15 (60.0%) patients with pemphigus foliaceus [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation